Efeitos de descontinuidades na propagação de ondas em estruturas unidimensionais - Vasques, Carlos Henrique [UNESP] (2013)
This work presents a study on wave propagation in one-dimensional structures, such as rods and beams, and analyses the effects of structural discontinuities on wave motion. The motivation of this project is the Structural Health Monitoring (SHM), technique used in engineering to detect the presence of damage in mechanical structures in several types of industries like: civil, automobile, aeronautical, thus, avoiding future problems and financial costs. There are several techniques for SHM application, and some of them use wave propagation. The use of waves is a tool sought by companies as a non-destructive technique and for being able to characterise geometric discontinuities. Elastic waves scatter their energy when they reach a discontinuity, and this is characterised by the reflection and transmission coefficients of the discontinuity. In this context, these coefficients are studied for two situations: with longitudinal waves guided by rods and with bending waves guided by beams. In this work, two different types of damage are modelled through basic mechanical elements such as mass, spring and damper. Additionally, structures with geometric discontinuity are investigated and compared with the models previously developed in order to gain physical insight into their dynamic behaviour